(untitled) (Annals of Bangladesh Agriculture, 2023)
Sixteen aman rice varieties were screened against two and three weeks of submergence based on their survival, growth and yield performance following split-plot design with three replications. Rice varieties AZ7006, BRRI dhan49, BRRI dhan52 and BRRI dhan57 exhibited the highest survival rate and minimum lodging that were associated with greater dry matter production under two weeks of submergence. Submergence affected the production of tillers, panicle and spikelets resulting lower grain yield than control. All the rice varieties except AZ7006 and BRRI dhan52 died under three weeks of submergence, where a small shoot of these varieties lived. These two varieties took longer time for producing shoot dry matter, tiller, panicle and maturity. Though they produced spikelets, but these were sterile due to low air temperature at flowering stage. Moreover, rice varieties BRRI dhan52, BRRI dhan57, BRRI dhan90 and AZ7006 under two weeks; and BRRI dhan52 and AZ7006 under three weeks of submergence acquired a combination of morphological and yield contributing response that ultimately induced a higher level of submergence tolerance. As the study revealed that BRRI dhan52 and AZ7006 were submergence tolerant, they could be incorporated in breeding program to develop rice variety for submergence tolerant up to three weeks. Ann. Bangladesh Agric. (2022) 26 (2) : 51-70